Cameo and Intaglio. Engraved Gems from the Sommerville Collection - Vermeule, Cornelius С.
Proto-Literate Stamp Seals, 1-3 — Early Mesopotamian Cylinder Seals, 4-13 — North Syrian Stamp Seals, 14-17 — Later Mesopotamian Seals, 18-24 — Phoenician and Related East Mediterranean Seals, 25-30 — Parthian, Sassonian and Related Seals, 31-48.